2015
DOI: 10.1017/s0963926814000789
|View full text |Cite
|
Sign up to set email alerts
|

Framework and form: burgage plots, street lines and domestic architecture in early urban Scotland

Abstract: ABSTRACT:This article explores some of the ways in which the closely regulated layouts and property boundaries within Scottish medieval towns may have influenced the form and character of domestic buildings during the late medieval and early modern periods. Drawing together strands of scattered evidence from archaeology, morphology, history and architecture, it re-examines how plot boundaries, main thoroughfares and subsidiary access passages acted as site constraints in relation to the design and configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The limited work on modelling VUD used raster-based remote sensing data (see, for example Lin et al, 2014; Zhang et al, 2017). Raster representations disregard the constraints and opportunities of the urban morphological frame on urban redevelopment (Siksna, 1997; Asami and Ohtaki, 2000; Wheeler, 2003; Stell and Tait, 2016). On the other hand, the relationship between parcel size and building height and density is evident according to the economy of scale associated with residential building construction (Ott et al, 2012).…”
Section: Overview Of Literature On Vudmentioning
confidence: 99%
“…The limited work on modelling VUD used raster-based remote sensing data (see, for example Lin et al, 2014; Zhang et al, 2017). Raster representations disregard the constraints and opportunities of the urban morphological frame on urban redevelopment (Siksna, 1997; Asami and Ohtaki, 2000; Wheeler, 2003; Stell and Tait, 2016). On the other hand, the relationship between parcel size and building height and density is evident according to the economy of scale associated with residential building construction (Ott et al, 2012).…”
Section: Overview Of Literature On Vudmentioning
confidence: 99%
“…Severe scrutiny was also applied to the construction of forestairs and turnpikes in public land, to give access to newly extended properties. 34 In Venice, extra space could be obtained through a fabbricato a barbacani, sloping outwards as it goes up and supported by wooden or stone corbels. 35 For more significant extensions, a sottoportego could be created with a house being built over the public street -here also on condition that the short arcade beneath would remain for public use.…”
mentioning
confidence: 99%
“…As infill development in Australia is generally informal, without any government policy focus, redevelopment, and specifically redevelopment on amalgamated lots, is understudied, with limited scholarly research into how amalgamation can be effectively used to reach urban consolidation targets. Previous research has analysed lot boundaries in various cities around the world, generally not in connection to urban consolidation targets but in establishing how cities change over time (see for example, Sanders and Schroder 2008;Sanders and Woodward 2015;Stell and Tait 2016) as well as changes to city blocks (see for example , Siksna 1998;Ryan 2008). A study of Auckland, New Zealand undertaken by Frederickson et al (2016) is one of few examples where property boundaries have been assessed in the context of reaching urban consolidation targets.…”
Section: The Research Problemmentioning
confidence: 99%
“…Throughout the United Kingdom, medieval lot boundaries have acted as site constraints from their inception, influencing the design and configuration of both individual building structures and groups of buildings (Stell and Tait 2016). In their study of Scottish towns, Stell and Tait (2016) found that lot boundaries in Scottish urban centres persisted over time, despite property pressures, with many lot boundaries and street frontages remaining very close to their original positions. These towns were originally laid out during the medieval period, and their stability over hundreds of years emphasises the permanent nature of property boundaries over time.…”
Section: Urban Morphologymentioning
confidence: 99%
See 1 more Smart Citation